2015
DOI: 10.1542/peds.2014-3966
|View full text |Cite|
|
Sign up to set email alerts
|

Weapon Involvement in the Victimization of Children

Abstract: OBJECTIVE: To report the prevalence of weapons involved in the victimization of youth with particular emphasis on weapons with a "high lethality risk" and how such exposure fits into the broader victimization and life experiences of children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
1
14
1
5
Order By: Relevance
“…Second, given our focus on WRVE, the violence composite we used was less broad than those used in other studies. However, we note that research on polyvictimization has shown that youth experiencing WRVE are substantially more likely to be experiencing other types of violence exposure (2), suggesting that WRVE may function as a proxy for other violence exposure types. Third, because our main goal was to examine the age-varying health implications of WRVE, our selection of health indicators was limited to a smaller set than may be ideal.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Second, given our focus on WRVE, the violence composite we used was less broad than those used in other studies. However, we note that research on polyvictimization has shown that youth experiencing WRVE are substantially more likely to be experiencing other types of violence exposure (2), suggesting that WRVE may function as a proxy for other violence exposure types. Third, because our main goal was to examine the age-varying health implications of WRVE, our selection of health indicators was limited to a smaller set than may be ideal.…”
Section: Discussionmentioning
confidence: 74%
“…Between 12%–26% of youth under 18 have experienced WRVE in their lifetimes (1, 2); 6%–8% of adolescents ages 14–17 report WRVE in the past year (3). Rates among young adults are also high; 12% of adults aged 18–27 have been exposed to past-year community violence, including weapon-related violent events such as seeing someone stabbed or shot, being threatened with a knife or gun, and being stabbed or shot themselves (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total cost of medical care, criminal justice proceedings, new security precautions, and reductions in quality of life associated with such crime amounts to over $174 billion annually in the US (Miller 2012). Alarmingly, about one in four school-age youth report having been a victim of at least one incident of weapon-involved violence (Mitchell et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…É subdividido em abuso sexual, abuso psicológico e abuso físico, que engloba a violência física como punição corporal, bater, empurrar, dentre outros (CDC, 2008). Por fim, a violência armada compreende a vitimização direta (envolvimento em brigas com uso de armas e vítimas de roubos, por exemplo) e vitimização indireta, como testemunhar esse tipo de violência (MITCHELL et al, 2015).…”
Section: Caracterização Da Violência E Fatores Associadosunclassified